PENGARUH REBRANDING DAN KUALITAS LAYANAN TERHADAP CITRA MEREK (Studi pada Pelanggan Majelis Mie Cabang Citarum, Surabaya) - WULAN SARI, CYINTIA (Jurnal Ilmu Manajemen (JIM), 2018)
The food industry has developed in major cities, especially in Surabaya, one of which is spicy noodle business, namely Majelis Mie so that business people are required to create strategies. One business strategy is rebranding. In addition to the rebranding of the noodle assembly, it also improves service quality so as to shape the brand image. The purpose of this study is to analyze and discuss the effect of rebranding and service quality on brand image. The sampling technique used is judgmental sampling. The sample used was 110 respondents. Respondents in this study were customers in the Majelis Mie of the Surabaya citarum branch starting from 18 years. The measurement scale uses a Likert scale with a closed questionnaire. Data analysis using multiple linear regression models. The results showed that there was a significant effect of rebranding and service quality on brand image. This is because the rebranding and service quality variables are proven to increase the brand image of the noodle in the minds of their customers. Keywords: brand image; rebranding; service quality